Analytical estimates of the lateral range of the descent and the optimal angle of the aircraft's roll - Антонова, А. О. (Proceedings of National Aviation University (archive), 2002)
The new analytical expressions of the dependence of the lateral range of the aircraft launch on the value of aerodynamic quality and the angle of the roll in the mode of quasi-stationary planning are considered. The dependence of the optimal angle of the machine's roll on its aerodynamic quality is analyzed